Circulating miR-338 Cluster activities on osteoblast differentiation: Potential Diagnostic and Therapeutic Targets for Postmenopausal Osteoporosis - Lin, Chujiao (Theranostics, 2019)
MicroRNAs (miRNAs) are the most abundant RNA species found in serum, and recently, several miRNAs have been found to be associated with osteoporosis. However, the development of such associated miRNAs into diagnostic and therapeutic targets remains unaddressed, mostly because of a lack of functional validation. Here, we identified circulating miR-338 associated with postmenopausal osteoporosis, and performed functional validation in vivo and in vitro. Methods: We collected the serum from postmenopausal osteoporosis patients (N=15) and female volunteers of the same age but with normal bone density (N=15) and examined the enrichment of miR-338 cluster. We also confirmed such enrichment using mice subjected to ovariectomy at different stages. We employed primary bone marrow stromal cells from mice and the MC-3T3 cell line along with CRISPR, RNA-seq and ChIP-qPCR to validate the biological function of secreted miR-338 cluster on osteoblastic differentiation and their upstream regulators. Moreover, we generated miR-338 knockout mice and OVX mice injected with an inhibitor against miR-338 cluster to confirm its biological function in vivo. Results: We observed a significant enrichment of miR-338 cluster in postmenopausal osteoporosis patients. Such enrichment was also prominent in serum from mice subjected to ovariectomy and was detected much earlier than bone density decreases revealed by micro-CT. We also confirmed the presence of an estrogen-dependent Runx2/Sox4/miR-338 positive feedback loop that modulated osteoblast differentiation, providing a possible explanation for our clinical findings. Moreover, deletion of the miR-338 cluster or direct intravenous injection of an miR-338 cluster inhibitor significantly prevented osteoporosis after ovariectomy. Conclusion: Circulating miR-338 cluster in the serum could serve as a promising diagnostic and therapeutic target for postmenopausal osteoporosis patients.